2014
DOI: 10.1186/1477-7819-12-142
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of AGBL2 expression and its inhibitor latexin in breast cancer

Abstract: BackgroundWe investigated the expression status of AGBL2 and its inhibitor latexin in breast cancer stem cells and its clinical implications in order to lay a foundation for managing breast cancer.MethodsCD44+/CD24- tumor cells (CSC) from clinical specimens were sorted using flow cytometry. AGBL2 expression status was detected in CSC and 126 breast cancer specimens by western blot and immunohistochemistry staining. The relationship between the AGBL2 protein and clinicopathological parameters and prognosis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…After pruning, we found 4 loci that were associated with both AD and fasting glucose at the genome wide significance level in the cross-trait meta-analysis ( Table 2). The first locus (index SNP: rs10501320, P meta =2.80×10 −16 ), was in close proximity to genes MADD, ACP2 and AGBL2, which was found to play roles in insulin sensitivity (Wagner et al 2011), lysosome and cerebellar function (van de Bunt et al 2015) and immune complexes (Zhang et al 2014). The second loci (index SNP: rs12805422, P meta =1.57×10 −13 ) was mapped to the genes C11orf94 and CRY2 which encode for a flavin adenine dinucleotide-binding protein involved in regulating the circadian clock.…”
Section: Ad and Fasting Glucosementioning
confidence: 99%
“…After pruning, we found 4 loci that were associated with both AD and fasting glucose at the genome wide significance level in the cross-trait meta-analysis ( Table 2). The first locus (index SNP: rs10501320, P meta =2.80×10 −16 ), was in close proximity to genes MADD, ACP2 and AGBL2, which was found to play roles in insulin sensitivity (Wagner et al 2011), lysosome and cerebellar function (van de Bunt et al 2015) and immune complexes (Zhang et al 2014). The second loci (index SNP: rs12805422, P meta =1.57×10 −13 ) was mapped to the genes C11orf94 and CRY2 which encode for a flavin adenine dinucleotide-binding protein involved in regulating the circadian clock.…”
Section: Ad and Fasting Glucosementioning
confidence: 99%
“…Furthermore, they showed that Lxn has a tumor-suppressive role and that it negatively regulates the expression of tumor-sustaining stem cell factors ( 19 ). Recently, Lxn has been demonstrated to be a tumor-suppressor gene in gastric cancer ( 38 ), hepatocellular carcinoma ( 39 ), melanoma ( 19 ), leukemia ( 40 ), prostate ( 41 ) and breast cancer ( 42 ). Our previous study revealed that Lxn induced the apoptosis and inhibited the proliferation of CD133 + MIA PaCa-2 pancreatic cancer cells ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously demonstrated that hypermethylation of CpG islands was found to be highly correlated with the transcriptional silencing of LXN gene (1416). Furthermore, consistent with its role as tumor suppressor, the LXN gene has been shown to be silenced by methylation in several different cancers (1416,3840). Our findings that demethylation treatment of the PCa cells restored LXN expression are consistent with these previous reports suggesting that methylation of the LXN gene contributes to its downregulation in the chemoresistant PCa cells.…”
Section: Discussionmentioning
confidence: 71%
“…LXN has homology to two other proteins/genes, tazarotene-induced gene 1 (TIG1) and cystatin C, both of which have been reported to be tumor suppressors (36,37). LXN expression has been suggested to be a tumor suppressor itself as it has been shown to inhibit tumor cell growth in gastric cancer (14), leukemia (15), melanoma (16), PCa (38), hepatocellular carcinoma (39) and breast cancer (40). In addition to being a potential tumor suppressor, LXN negatively regulates hematopoietic stem cell self-renewal in mice, resulting in an inverse relationship between LXN expression and HSC population size (17,18,41).…”
Section: Discussionmentioning
confidence: 99%